Pandemic Fatigue and Anxiety Sensitivity as Associated Factors With Posttraumatic Stress Symptoms Among University Students in South Korea During the Prolonged COVID-19 Pandemic - Hee Jun Kim; Timothy J. Meeker; Ingrid K. Tulloch; Jake Mullins; Jin-Hee Park; Sun Hyoung Bae (International Journal of Public Health, 2022)
Objectives: The global impact of COVID-19 driven by new variants may add to the negative mental health consequences of the prolonged pandemic, including posttraumatic stress symptoms (PTSS). University students may be prone to develop a series of PTSS due to life plan disruptions as well as increased uncertainty caused by the pandemic. The purpose of this study was to assess the associations between pandemic fatigue, anxiety sensitivity (AS), and PTSS among university students in South Korea.Methods: Using convenience sampling, 400 students participated in this cross-sectional online survey. Descriptive statistics and linear mixed models were used to examine factors associated with PTSS.Results: About one-third (32.3%) of the participants reported clinically significant levels of PTSS. Multivariate analyses revealed that pandemic fatigue (β = 0.124, p < 0.001) and AS (β = 0.212, p < 0.001) were significantly associated with PTSS while controlling for other study variables.Conclusion: Young adults who feel more fatigue related to the COVID-19 pandemic and with high AS should be given access to mental health resources to better manage their mental health and reduce PTSS.